G-Protein coupled receptors in drug discovery - Wigglesworth, Mark (Henry Stewart Talks, 2014)
The G-protein coupled receptor superfamily, GPCRs as drug targets, Approved GPCR drugs, why the reduction in GPCR drugs, new screening technologies and new drug targets